2017
DOI: 10.1093/ndt/gfx242
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in 145 patients with assumed benign immunoglobulin A nephropathy

Abstract: We have shown that 18.6% of patients with assumed benign IgAN had progressive disease after a median duration of 22 years and that these patients could not be predicted at the time of biopsy. Our study demonstrates that an extended follow-up period is needed when assessing prognosis in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…Although long-term renal prognoses of kidney diseases are clinically relevant, there is no established histopathological factor to predict the long-term renal prognosis of IgA nephropathy (IgAN). Knoop et al used data from the Norwegian Kidney Biopsy Registry and found that none of the histopathological variables at the time of biopsy could identify patients with long-term progressive disease [1]. Coppo et al conducted long-term follow-up analyses of the original Validation Study of the Oxford Classification for IgA Nephropathy cohort, and showed an independent relationship between kidney biopsy findings and the risk of progression towards kidney failure in patients with IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…Although long-term renal prognoses of kidney diseases are clinically relevant, there is no established histopathological factor to predict the long-term renal prognosis of IgA nephropathy (IgAN). Knoop et al used data from the Norwegian Kidney Biopsy Registry and found that none of the histopathological variables at the time of biopsy could identify patients with long-term progressive disease [1]. Coppo et al conducted long-term follow-up analyses of the original Validation Study of the Oxford Classification for IgA Nephropathy cohort, and showed an independent relationship between kidney biopsy findings and the risk of progression towards kidney failure in patients with IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy how old many registries are. These old registries allow for studies about the long-term course of kidney disease and underline the usefulness of kidney biopsy registries [ 44 , 45 ]. The age of the registries is also reflected by the coding systems and mappings used.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline patient characteristics (estimated glomerular filtration rate (eGFR), age, 24-h proteinuria) in Oxford validation studies [7,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72]. …”
Section: Figurementioning
confidence: 99%
“…The 10-year renal survival rate reported by different registries varies between 60% and 95%, while up to 50% may reach end-stage renal disease (ESRD) within 20 years of diagnosis [4,5,6]. Moreover, even those patients initially considered to have a “benign” disease show a progressive decline of renal function if followed for more than 20 years [7]. Regional environmental factors, differences in racial composition, and genetic susceptibility are important contributors to IgAN epidemiology and might explain disease susceptibility, heterogeneous presentation, and the risk of progression [8].…”
Section: Introductionmentioning
confidence: 99%